The Influence of Emotional Intelligence and Individual Characteristics on the Performance of Employees of the Department of Cooperatives, Micro, and Small Enterprises, Industry and Trade, Banjar Regency, South Kalimantan - Fatimah, Siti; Audah, Ali; Kadir, Abdul; Naimah, Naimah; Syarqawie, Fithriana (Universitas Hang Tuah, 2025)
This study aims to analyze the influence of emotional intelligence and individual characteristics on employee performance, both simultaneously and partially, and to identify the most dominant variable affecting the performance of employees at the Office of Micro Enterprises, Industry, and Trade of Banjar Regency, South Kalimantan. The research employed a quantitative approach with a survey method and multiple linear regression analysis. A total of 39 respondents were selected using the total sampling technique. The results show that emotional intelligence and individual characteristics simultaneously have a significant effect on employee performance. Partially, both variables also positively and significantly influence performance, with individual characteristics being the most dominant factor. This finding implies that employees with strong characteristics including work motivation, responsibility, self-confidence, and aligned personal values are more capable of performing tasks professionally and consistently in accordance with the principles of equal and fair public service. These findings reinforce human resource management theories that highlight the importance of personal attributes and emotional competence in supporting individual performance. Furthermore, the results align with Law No. 43 of 1999, which emphasizes professionalism as a guiding principle in the recruitment and assignment of civil servants. The study recommends that organizations enhance their recruitment, training, and employee development programs by focusing on strengthening individual characteristics and emotional intelligence as key assets to improve the performance of civil servants.